Mapping the ‘Magic of Huesca’: a methodological proposal for the design of tourist cartography - María Caudevilla Lambán; Raúl Postigo Vidal; María Zúñiga Antón (Journal of Maps, 2023)
ABSTRACTMaps published for tourism promotion and information constitute a particular sub-group of tourist maps made using Geographic Information Systems (GIS). This paper proposes a methodological protocol for the systematic elaboration of tourism mapping. This procedure is applied to the design of the tourist map of the province of Huesca. The cartographic tool was designed based on the needs of tourism promotion by the Public Administration, seeking the halfway point between persuasion and precision when representing elements on the map. Given that data would have to be updated and modified in the future, open-source software was used so that the administration can then run, modify and update it. In addition, the project was validated through surveys to two different audiences (general and expert).